Palladium–Polypyrrole Nanocomposites Pd@PPy for Direct C–H Functionalization of Pyrroles and Imidazoles with Bromoarenes - Bizouard, Pierre; Testa, Christelle; Zinovyeva, Veronika A.; Roger, Julien; Hierso, Jean-Cyrille (Synlett, 2016)
Palladium–polypyrrole nanocomposites (Pd@PPy) with unique combination of high palladium dispersion (nanoparticle size 2.4 nm) and high palladium content (35 wt%) are efficient catalysts for the selective arylation of substituted pyrroles and imidazoles with either activated or deactivated aryl bromides. The performances of the recoverable supported palladium catalyst matches the best performances of homogeneous systems based on Pd(OAc)2 at 0.5–0.2 mol%, and largely overwhelm the classical Pd/C catalyst.
Keywords: palladium; polypyrrole; nanocomposite; C–H arylation; azoles